As práticas pedagógicas em educação para os direitos humanos no cotidiano da escola municipal zumbi dos palmares - Gomes, Solange Moura (2016)
The present study aimed to investigate the impacts of pedagogical practices of education in/for the human rights in prevention and coping of violence in the daily life of the School Zumbi dos Palmares, in João Pessoa- PB. The methodological approach adopted was the qualitative one, from a case study, associated with document analysis and bibliographic. Reference in the design of the pedagogical dimension of Human Rights as a priority field for the theoretical distribution, historical and methodological of Human Rights, highlighting, in this context, the intercultural perspective of Human Rights. Paulo Freire, and other great thinkers of Human Rights, leads the nuclear axis of theoretical framework who dares to think of history as a possibility and not as determination, and the school as a space of the production of knowledge. It shows the construction, in Brazil, of public policies for Human Rights: the introduction of the Human Rights as a crosscutting theme in formal education in Brazil, incorporating the principles of the Universal Declaration of Human Rights in the Law of Guidelines and Bases of National Education (LDB nº 9.394/1996), as well as the regulation of education in / for Human Rights by MEC ((Resolution/CNE/CP nº1/2012). Points out the challenge to overcome the discourse of dialogue and respect to human dignity beyond the theory and school space, in a reality marked by violence and social exclusion. Finally, argues that education in / for Human Rights, directed to the emancipation of the individuals, extrapolates the condition of educational policy intention of school, to become a social right and human systematized from the pedagogical practices in everyday school life.